REPRESENTASI KECEMASAN DAN KEPUTUSASAANDALAM VIDEO KLIP NADIN AMIZAH - SEPERTI TULANG(Kajian Semiotika Roland Barthes) - Gerardus Her Utama Anggara Dadi, (2020)
Mental health problems become a problem that often afflicts young people, but at the time of discussing mental health problems not yet known. This has increasingly encouraged many workers to voice mental health issues through art formations. The development of elderly people's expression is now growing rapidly and many are issued by visual communication, one of them in music videos or video clips. The purpose of this study is to study the representation of health problems such as anxiety and despair. The purpose of this study was to determine the representation of mental health issues such as anxiety and hopelessness through the study of Roland Barthes's semiotics. This research uses descriptive qualitative method. In this research, the analytical study used is the video clip "Nadin Amizah - Seperti Tulang". The research data were obtained through observation from the video clip analysis unit "Nadin Amizah - Seperti Tulang Roland Barthes uses the terms denotation and connotation in describing the relationship between signifier and signified. The results of this study prove that the representation of anxiety and hopelessness in the video clip "Nadin Amizah - Seperti Tulang " is true and represented by signs contained in several scenes both visualized through video and singing from the lyrics of the song Nadin Amizah - Seperti Tulang.